When the music stops: the impact of terrorism on Malian youth (United Nations Interrional Crime and Justice Research Institute, 2020)
'This report is part of a project jointly carried out by the United Nations Interregional Crime and Justice Research Institute (UNICRI) and the International Centre for Counter-Terrorism - The Hague (ICCT). Through field research and primary data analysis it aims to advance knowledge and awareness on the issue of violent extremism in Mali through the lenses and voices of the country's youth. The report explores the impact that terrorist groups had on young people. It offers new insights on the impact of terrorism on youth, whose lives have been significantly impacted by terrorism."